2009
DOI: 10.1179/175158409x459967
|View full text |Cite
|
Sign up to set email alerts
|

Failure analyses of cemented tungsten carbide extrusion die

Abstract: In this study, the failure of a cemented tungsten carbide extrusion die (WC-Co) which was designed for the production of 55 000 components but failed during production of third component has been investigated. The die is used for cold extrusion of auto parts components as sizing die. Sizes achieved by forging process are further refined to required fine tolerance. The component size is required to be controlled within ¡20 mm. The investigations revealed that the failure is due to abusive machining of cemented … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…A Lanzuttia et alInvestigated the influence of failure analysis on cemented carbide specifically looking at material characterization, numerical analysis, and material modeling [33].According to the authors opinion [33]further proposes limiting factor analysis used for cold rolling which was also performedon detailed investigation by mechanical materials testing mechanisms where specimens were subjected to fractographic examination using optical microscope [70] and scanning electron microscopy and energy-dispersive X-ray spectroscopy (SEM + EDXS), these approach are very useful and require a special care for gathering effective information about the findings [22], [35], [43]. However in current hard metals complex microstructurerequires better advanced resolution than that obtainable by light optical microscope (LOM) [71].Fatigue-crack growth can be recognized by those shaped made by unstable fracture and investigations that reveal the region conforming to fracture surfaces using scanning electron microscope.…”
Section: Fatigue Behavior Of Cemented Carbidementioning
confidence: 99%
“…A Lanzuttia et alInvestigated the influence of failure analysis on cemented carbide specifically looking at material characterization, numerical analysis, and material modeling [33].According to the authors opinion [33]further proposes limiting factor analysis used for cold rolling which was also performedon detailed investigation by mechanical materials testing mechanisms where specimens were subjected to fractographic examination using optical microscope [70] and scanning electron microscopy and energy-dispersive X-ray spectroscopy (SEM + EDXS), these approach are very useful and require a special care for gathering effective information about the findings [22], [35], [43]. However in current hard metals complex microstructurerequires better advanced resolution than that obtainable by light optical microscope (LOM) [71].Fatigue-crack growth can be recognized by those shaped made by unstable fracture and investigations that reveal the region conforming to fracture surfaces using scanning electron microscope.…”
Section: Fatigue Behavior Of Cemented Carbidementioning
confidence: 99%
“…Numerous investigations on the friction and wear properties of cemented carbide and CVD coatings for mold and tool applications have been done [ 11 , 12 , 13 , 14 , 15 , 16 ]. Khatter et al [ 17 ] investigated the cause of failure in cemented carbide extrusion dies and indicated that the failure occurred as a result of aggressive cemented carbide machining. In addition, according to experiments under different machining conditions on cemented carbide materials, the optimal machining settings have been found, and a new die has been developed and manufactured, which exhibits high performance.…”
Section: Introductionmentioning
confidence: 99%